HISTORY OF PHYSICAL EDUCATION IN PERU (Fiep Bulletin - online, 2013)
The practice of physical activity has been present since the pre-Inca period. Proof of this are the several manifestations found in the various ceramics (huacos) of the Mochica, Nazca, Tiahuanaco Vicús cultures. These physical activities were related to military water activities performed at sea. The writings of the Spanish conquest chroniclers make references to physical activities in the Inca Empire, such as the Warachicuy, Inti Raymi, practice of ball games and the participation of Chasquis. The Inca road system, whose purpose was religious and ceremonial, included a pilgrimage of the Inca. Nowadays, this road system includes the trail to Machu Picchu, a 42-kilometer route still frequented by many tourists. During the Spanish influence period, the practice of physical activities decreased as it was not in the interest of the conquerors. However, Garcilaso de la Vega relates that Gonzalo Pizarro used to organize running and jumping competitions, among other athletic practices, for the first-generation young mestizos. In the end of the Viceroyalty (1779 – 1780), the diocese of Trujillo staged ball games that had many of the current hockey fundamentals.